The Impact of Competency on the Performance of Homecare Nurses in Bandung City - Jaelani, Ahmad; Dewi Ayu, Windri; Wati, Eti (Jurnal Vocational Nursing Sciences (VNUS), 2025)
In Indonesia, homecare services have become increasingly popular due to their flexibility and cost-effectiveness, particularly for individuals requiring long-term care, such as patients with degenerative diseases. The quality of homecare services is closely tied to the performance of nurses, who serve as the frontline providers of healthcare in this setting. This study aims to examine the effect of nurses’ competency levels on their performance within homecare service providers in Bandung City. A descriptive explanatory survey design was employed to analyze the relationship between nurse competency and performance. The study population included all 99 nurses working in homecare service providers in Bandung. A non-probability sampling technique was used to include the entire population. Nurses’ performance was evaluated across four key dimensions: quantity of output, quality of output, timeliness, and attendance. The total performance score was 2,475 (61.16%). Among these, the quantity dimension scored the lowest, while quality was the highest. Regression analysis revealed a beta coefficient of -0.021, and the partial test showed a t-value of 2.56, exceeding the critical value of 1.65. Although homecare nurses in Bandung demonstrate high competency, the statistical analysis indicates a significant yet negative correlation between competency and performance. This suggests that decreases in competency are associated with lower performance levels among homecare nurses in Bandung City.